Midterm outcomes of endovascular treatment with bare metal stents for Leriche syndrome patients. (21st November 2020) - Zhang, Bihui; Niu, Guochen; Yan, Ziguang; Zou, Yinghua; Tong, Xiaoqiang; Yang, Min
Abstract: OBJECTIVES: This study was undertaken to evaluate the acute and midterm results of endovascular treatment with bare metal stents (BMS) for Leriche syndrome patients. METHODS: Patients with Leriche syndrome treated with BMS from August 2008 to May 2017 were included in the study and followed up. The primary endpoints were primary restenosis-free survival rates at 1, 2 and 3 years. The secondary endpoints were secondary restenosis-free and freedom from target lesion revascularization survival rates at 1, 2 and 3 years; technical success rate; complication rate; procedure-related mortality rate; and clinical status improvement at follow-up. RESULTS: Twenty patients were included and the follow-up duration was 34.7 ± 18.7 months (0–86 months). The 1-, 2- and 3-year primary restenosis-free survival rates were 94.4%, 88.1% and 73.5% and the secondary patency rates were 94.4%, 94.4% and 86.6%, respectively. The freedom from target lesion revascularization survival rates of patients at 1, 2 and 3 years were 94.4%, 88.1% and 79.3%, respectively. The aortoiliac lesions were successfully treated with BMS bilaterally in 17 patients (85.0%) and unilaterally in another 3 patients (15.0%). The complication rate was 10.0% and the procedure-related mortality rate was 0%. Mean ankle-brachial index increased significantly from 0.43 ± 0.20 before the procedure to 0.95 ± 0.21 after the procedure ( P  < 0.001), and to 1.00 ± 0.19 at the end of the follow-up ( P  < 0.001). Improvement in symptoms occurred in most patients soon after the endovascular procedure (95.0%) and at follow-up (88.2%). CONCLUSIONS: Endovascular treatment with BMS is effective and safe for patients with Leriche syndrome according to 3-year follow-up results.